Scenario-Driven Safety Verification: A Comprehensive Framework for Autonomous Vehicle Validation within ISO 26262 - Yuvaraj J Patil, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a methodological framework for scenario-driven safety verification in automotive systems, with specific emphasis on its integration within the ISO 26262 functional safety standard. It focuses on advanced driver assistance systems (ADAS) and autonomous driving functions, detailing how diverse driving scenarios—including varied road conditions, traffic situations, weather conditions, and potential vehicle faults—are defined and simulated to ensure comprehensive safety validation. The framework leverages virtual simulation and hardware-in-the-loop environments to implement key processes including scenario definition, safety analysis, and risk mitigation. By establishing robust links between test scenarios and specific ISO 26262 safety goals, the approach enables rigorous risk assessment and seamless integration into verification and validation workflows. While addressing challenges such as scenario complexity, coverage analysis, and computational overhead, this article demonstrates how early hazard identification and thorough validation strengthen automotive functional safety assurance. This provides practical insights for implementing scenario-driven verification within the ISO 26262 context, contributing to enhanced safety validation practices in autonomous vehicle development.
Keywords: Functional Safety Verification; Autonomous Vehicle Testing; Scenario-Based Analysis; ISO 26262 Compliance; Safety Goal Validation